Exploring kindergarten teachers’ perspectives in parental involvement in the Philippines - Bartolome, Melissa Tiglao; Mamat, Nordin; Masnan, Abdul Halim (Southeast Asia Early Childhood Journal, 2020)
In this descriptive qualitative study, parental involvement is the partaking of families on the learning and holistic development of children at home and in school on teachers lens and a part of a larger study. Teachers’ perspective is imperative in developing a school-facilitated parental involvement framework in the Philippine context. The researcher used document analysis and interview to gather data. Data were analyzed using content and thematic analysis. Results revealed four themes; (i) meaningful home-school communication; (ii) collective in-school engagement; (iii) structural at-home learning support; and (iv) refining teachers’ capacity. These results can be used as an input in developing a school-facilitated parenting involvement framework that encompass the contribution of teachers in planning, developing, and evaluating parental involvement programs which future researchers can also use in their studies. It is important that teachers especially early childhood educators should understand parental involvement and recognize its positive effects to the teaching and learning process.